Efektifitas Undang-Undang Perlindungan Konsumen Dalam Memberikan Perlindungan Hukum Bagi Pengguna E-Commerce Di Era Ekonomi Digital - Bintarawati, Fenny; Rismana, Daud (Fakultas Hukum Universitas Mulawarman, 2024)
The condition of world economic development has entered a new period, referred to as the digital economy. This is seen from The growing quantity of financial transactions conducted via the internet. One example is trading through internet media or e-commerce. Facing the characteristics of e-commerce, there is a possibility that there will be disputes related to the law in online transactions. This e-commerce transaction does not only occur in a country, so it is necessary to analyze whether the existence of Law No. 8 of 1999, which addresses consumer protection in the digital economy era is still effective or not in providing legal protection to e-commerce consumers. This study's goal is to be able to contribute to the study of Consumer Protection law related to how to implement the Consumer Protection Law (UUPK) in the digital economy era, and whether it is still effective if implemented in the current digital economy era. This research method uses an empirical juridical type, which analyzes applicable provisions and regulations by examining various legal sources and literature sources as a reference based on a phenomenon that occurs or develops in society. The study's findings demonstrate that in its implementation, the Law that Protecting Consumers cannot accommodate various kinds of problems that occur in the current digital economy era such as e-commerce customer data leaks, fraud through e-commerce, etc. Meanwhile, related to its effectiveness, it is considered ineffective in providing legal safeguards for e-commerce customers because the rules in this UUPK in guaranteeing consumer rights are still very limited to conventional buying and selling. The update of the rules in the UUPK must be carried out immediately by the Government in order to adapt to the current digital economy conditions.